Implementasi dan Perancangan Sistem Informasi Penjualan Vapestore Berbasis Mobile Flutter - Ripai, Rizki; Fauzi, Yudiansyah; Sidik, Fazar; Aldi Pari, Riki; Hamdan, Rifky Aditia (Jurnal Informatika dan Rekayasa Perangkat Lunak, 2024)
The sale of vape products has become a rapidly growing industry, with ever-increasing demand from an increasingly diverse range of consumers. To keep up with these developments, having an efficient and easily accessible sales information system is important for vape shop owners. This research aims to implement and design a mobile-based Vapestore sales information system using Flutter. The system development method used in this research is an iterative software development method. Flutter was chosen as a development platform because of its ability to create mobile applications with responsive user interfaces and efficient cross-platform deployment. The information system designed will include features such as inventory management, customer management, generating sales reports, as well as online payment integration. By using Flutter, it is hoped that this application can be easily accessed via various mobile devices such as smartphones and tablets, so that shop owners can manage their sales efficiently wherever and whenever they need. Apart from that, with the online payment integration feature, customers will also get a more comfortable and faster shopping experience. It is hoped that this research will make a positive contribution to vape shop owners in increasing their operational efficiency and improving the customer shopping experience. Apart from that, the results of this research can also be a reference for further research in developing a sales information system that is more sophisticated and in line with the needs of the ever-growing market.